Synthesis And Characterization Of Potential Human Hypoxia Inducible Factor (Hif) Prolyl Hydroxylase Domain 2 (Phd-2) Inhibitors - Toh, Lee Roy (2021)
Pharmacological inhibition of prolyl hydroxylase domain (PHD) enzymes have been suggested as an alternative method to upregulate hypoxia inducible factor (HIF) and serve as a therapeutic method for diseases such as anemia and cardiovascular disease. This study aims at evaluating five series of compounds: 2H-chromene-3-carboxylic acids (A1 – A3), triazine (B), pyrimidine (C), benzenesulfonamides (D1 – D4), and benzoxazolamine (E1 – E3) as PHD-2 inhibitors. The binding modes and free energies of A1 – E3 were first evaluated using molecular docking studies. The docking results demonstrated that all the tested compounds were capable of binding to the PHD-2 active site in a bidentate manner and forming salt bridge interaction with amino acid residue Arg383 apart from displaying preferential free energies of binding. The compounds were subsequently synthesized and characterized using FT-IR, HRMS, 1H NMR, 13C NMR and 2D NMR to confirm the structures. A1 – E3 were then screened for their inhibitory potencies against PHD-2 using a PHD-2 RapidFire assay. The inhibitory results revealed that compound E1 was a potent PHD-2 inhibitor, with IC50 value of 17.45 μM. On the other hand, ethyl ester E2 and E3 were synthesized and tested in cell-based study. However, they showed no ability to induce HIF-1α as an indicator of cellular PHD-2 inhibition.